Efeitos da Bifidobacterium longum 51A sobre o restabelecimento da homeostase intestinal, em modelo experimental de colite ulcerativa induzida por DSS - Fernanda Alves Abrantes (2015)
Ulcerative colitis is an inflammatory bowel disease characterized by periods of remission and recurrence of intestinal inflammation, resulting in intermittent abdominal pain, diarrhea and fever. There are reports in literature demonstrating that probiotics are capable of inducing beneficial effects on intestinal epithelium. Thus, the purpose of this study was to evaluate the effect of Bifidobacterium longum 51A (BL51A) administration in BALB/c mice with ulcerative colitis induced by dextran sodium sulfate (DSS). For this, colitis was induced by administration of DSS solution (3.5%) for seven days. Animals belonging to preventive/curative group received by gavage, 0.1 mL of BL51A (108 CFU) before and during colitis induction, while, animals in curative group, only received BL51A during colitis induction. During disease induction period, DSS consumption, weight variation, consistency and presence of blood in the stool were evaluated. After this period, mice were anesthetized [xylazine (8 mg/kg) and ketamine (60 mg/kg) solution], euthanized, and blood, intestinal fluid and colon were collected for carrying out analyzes. Parameters such as intestinal permeability (IP), colon length, injury extent and histological studies of intestinal epithelium were investigated. In addition, cytokines (IL-1, IL-10), chemokines (CXCL1 (KC), CCL11) and secretory immunoglobulin A (sIgA) measurements were performed. Neutrophils and eosinophils infiltrate were indirectly investigated through MPO and EPO enzymes evaluation, respectively. DSS administration resulted in animals weight lost (p<0.001), increased clinical score (p<0.05), IP (p<0.01), IL-1 cytokine (p<0.05), CXCL1 (p<0.01) and CCL11 (p<0.001) chemokines, MPO and EPO enzymes (p<0.001), and also sIgA (p<0.001), as compared to control group. Furthermore, disease induction resulted in intestinal epithelium changes, submucosa edema, mucosal lesions and inflammatory infiltrate. Animals that received Bifidobacterium longum 51A curative treatment showed reduced lesion extension (p<0.01), IL-1 (p<0.001) and MPO (p<0.05) levels reduction, higher intestinal epithelial preservation and lower edema intensity compared with DSS group. Preventive/curative treatment only contributed to EPO (p<0.001) and injury extension (p<0.01) reduction. Curative treatment was more effective in reducing some aspects related to inflammatory response intensity, however, did not produce beneficial effects on clinical parameters evaluated and neither reduced IP in experimental colitis.